Ajax Based Exam Engine with Tagging System to Improve Learning - Asroni, Asroni; Abdurrahim, Minhajuddin K.; Damarjati, Cahya (Universitas Muhammadiyah Yogyakarta, 2020)
In this paper, we propose exam engine software with tagging system to help students’ study. With this tagging system, they can analyze their subject learning through exam they have done from time to time. When the students see their reports, the students will decide which subjects are low in grade and should be re-studied. We use AJAX technology to enrich the user experience of this exam engine. After we test all feature with unit testing, this exam engine is proven to runs well and do benefits for students.